Angry neighbors [videorecording (DVD)] - Bear, James M.; Torabpour, Hamid; Langella, Frank; Channing, Stockard; Parker, Katie; Marin, Cheech; Benson, Ashley, 1989-; Cannavale, Bobby; Rosenblatt, Roger (Lionsgate, 2023)
When his ultra-wealthy neighbor in the Hamptons builds an obnoxious mega-mansion next door, grumpy retired novelist Harry March concocts an elaborate scheme for revenge that is destined to go hilariously awry.